An extensible and configurable trace–driven web server cluster simulation platform. (10th April 2015) - Xiong, Zhi; Liu, Weijun
Scheduling algorithm and cache replacement algorithm are two important aspects in a web server cluster, which affect, even determine, the performance of the cluster system. However, their performance depends on client access pattern and some key system parameters to a large extent. In this paper, we design and implement a trace–driven web server cluster simulation platform based on JavaSim, called WSCSim, to evaluate the two kinds of algorithms. The algorithms are directly written in Java, so complicated algorithms can be simulated. In the platform, users are allowed to add new trace parsers to support different trace formats, and can utilise the timer and hook component to collect related information and then calculate the performance indexes they are interested in. Especially, the platform adopts loosely–coupled component architecture to facilitate extension, and all the extensible components are plug and play (PnP). All the components and their parameters can be configured in a configuration file of XML format. Two simulation application scenarios show the feasibility and validity of WSCSim.